Use of gain-of-function suppressor screening to elucidate Candida albicans Cdr1 efflux mechanism, inhibition, and drug resistance - Zhao, Mengcun; Niimi, Masakazu; Cannon, Richard D.; Lamping, Erwin (Frontiers in Microbiology, 2025)
The ATP-binding cassette (ABC) transporter Cdr1 is a key mediator of antifungal drug resistance in Candida albicans, a major pathogen responsible for invasive candidiasis. Cdr1 belongs to the pleiotropic drug resistance (PDR) ABC transporter subfamily, exhibits broad substrate specificity, and plays a central role in protecting C. albicans cells from azole drugs and many other xenobiotics. Although high-resolution structures of Cdr1 and its homologs are now available, the transport cycle of Cdr1 remains incompletely understood. Furthermore, although these structures provide valuable information about the spatial arrangements of amino acids, they do not reveal how, and which, amino acid interactions affect pump function and how to relieve drug resistance. Drug resistance–based gain-of-function suppressor screening has emerged as a powerful tool to identify inhibitor binding hotspots, and conformational adaptation mechanisms. These studies reveal residues critically important for the structural and functional integrity of Cdr1, offering deeper mechanistic insights into substrate/inhibitor recognition and transport. Importantly, these insights will aid in the rational development of Cdr1 inhibitors that, when combined with azoles, may reverse efflux pump-mediated drug resistance. Inhibitors that stabilize discrete conformations of Cdr1 offer additional tools for the structural and mechanistic characterization of this important efflux pump. Here, we demonstrate the power of gain-of-function suppressor screening for determining functionally important residues and validating structural models of the prototype fungal PDR transporter, C. albicans Cdr1.